Frivolity Theatre - "Ghent, Jaz" "Chadwick, Katherine"
Granny Firewall is half-dragon and is the oldest of the very odd McCorkle family. After getting a mysterious message by seagull Granny and her grandchildren, Hamish and Eugenie, travel back in time to help out some of Granny's old friends at the once glorious Frivolity Theatre. But evil Uncle Weaver is still lurking and planning on causing trouble. Suggested level: primary
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Time travel Fiction